Myofibroblasts derived type V collagen promoting tissue mechanical stress and facilitating metastasis and therapy resistance of lung adenocarcinoma cells - Guangsheng Zhu; Yanan Wang; Yingjie Wang; Hua Huang; Boshi Li; Peijie Chen; Chen Chen; Hongbing Zhang; Yongwen Li; Hongyu Liu; Jun Chen (Cell Death and Disease, 2024)
Abstract Lung cancer is a leading cause of cancer-related mortality globally, with a dismal 5-year survival rate, particularly for Lung Adenocarcinoma (LUAD). Mechanical changes within the tumor microenvironment, such as extracellular matrix (ECM) remodeling and fibroblast activity, play pivotal roles in cancer progression and metastasis. However, the specific impact of the basement membrane (BM) on the mechanical characteristics of LUAD remains unclear. This study aims to identify BM genes influencing internal mechanical stress in tumors, elucidating their effects on LUAD metastasis and therapy resistance, and exploring strategies to counteract these effects. Using Matrigel overlay and Transwell assays, we found that mechanical stress, mimicked by matrix application, augmented LUAD cell migration and invasion, correlating with ECM alterations and activation of the epithelial-mesenchymal transition (EMT) pathway. Employing machine learning, we developed the SVM_Score model based on relevant BM genes, which accurately predicted LUAD patient prognosis and EMT propensity across multiple datasets. Lower SVM_Scores were associated with worse survival outcomes, elevated cancer-related pathways, increased Tumor Mutation Burden, and higher internal mechanical stress in LUAD tissues. Notably, the SVM_Score was closely linked to COL5A1 expression in myofibroblasts, a key marker of mechanical stress. High COL5A1 expression from myofibroblasts promoted tumor invasiveness and EMT pathway activation in LUAD cells. Additionally, treatment with Sorafenib, which targets COL5A1 secretion, attenuated the tumor-promoting effects of myofibroblast-derived COL5A1, inhibiting LUAD cell proliferation, migration, and enhancing chemosensitivity. In conclusion, this study elucidates the complex interplay between mechanical stress, ECM alterations, and LUAD progression. The SVM_Score emerges as a robust prognostic tool reflecting tumor mechanical characteristics, while Sorafenib intervention targeting COL5A1 secretion presents a promising therapeutic strategy to mitigate LUAD aggressiveness. These findings deepen our understanding of the biomechanical aspects of LUAD and offer insights for future research and clinical applications.